Contrast-Induced Nephropathy in 118 Coronary Angiographic Cases - Haque, AFM Shamsul; Rabbani, Md Golam; Hossain, Muhammad Rabiul; Rashid, Md Hayder; Mostafi, Mamun; Rahman, AKM Mijanur (Journal of Medicine, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Contrast-induced nephropathy (CIN) is the third leading cause of hospital-acquired renal failure and is associated with significant morbidity and mortality. The aim of the present study was to find out the incidence and outcome of CIN in patients undergoing coronary angiography using standard cardiac cath lab protocol. This observational study was carried out in patients undergoing Coronary angiography with or without Percutaneous coronary interventions (PCI) in CMH Dhaka from July 2007 to July 2008. Exclusion criteria were chronic kidney disease (CKD), nephrotoxic medications, severe hypotension, severe heart failure (NYHA class IV) and severe anaemia. Out of 118 cases two demonstrated impaired renal function and both of them were diabetic. The incidence was found to be 1.69 % and outcome was satisfactory in these cases. Renal function of both the patients gradually became normal within next two weeks. No patient required dialysis. doi: 10.3329/jom.v10i2.2822 J MEDICINE 2009; 10 : 94-96